Method for preparing fiber membrane with three-dimensional fold microstructure and application
By using a liquid medium receiving device in electrospinning technology, a fiber membrane with a three-dimensional wrinkle structure is prepared, which solves the problem of microstructure construction complexity in the prior art and improves the performance of the flexible sensor.
Patent Information
- Application Number
- CN202411366149.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-31
AI Technical Summary
In the prior art, when preparing microstructures of flexible substrate materials, secondary processing increases the process complexity, making it difficult to effectively construct a three-dimensional wrinkle structure to improve the sensing performance of the flexible sensor.
By changing the receiving device in electrospinning technology, changing from solid medium to liquid medium to receiving, using water or aqueous solution to form a three-dimensional wrinkle structure during the collection process, combining metal needles and appropriate spinning parameters, a three-dimensional wrinkle has been prepared. Microstructured fiber membrane.
The three-dimensional wrinkle structure of the fiber membrane is simply and controllable in traditional electrospinning technology, and the performance of the fiber membrane in pressure sensors and strain sensors is improved, especially the regulation of stress sensitivity and strain range.
Smart Images

Figure CN119221208A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field, and specifically relates to a method for preparing a fiber membrane with a three-dimensional wrinkled microstructure and an application thereof. Background Art
[0002] In recent years, a large number of research results have shown that electrospinning technology has brought unique advantages to the preparation of flexible mechanical sensors, such as flexibility of the method, high efficiency of the preparation process, fit of the substrate material to the skin, breathability, etc. However, most of the related work is devoted to exploring the effects of the types of electrospinning materials, the types of sensitive element materials, and the overlap methods between sensitive elements on the sensing performance. In fact, the microstructure of the flexible substrate material also has a great influence on the stress sensing performance. A large number of literatures have proposed methods to improve sensor performance by constructing microstructures on polymer substrates. For example, Lei Peng et al. (Advanced Fiber Materials, 2024, 6, 414-429) proposed to construct a wrinkled structure on a PU fiber membrane by pre-stretching VHB tape to improve the pressure sensing performance of the composite fiber membrane; Cao Zhenpeng et al. (Nanomaterials, 2023, 13(7), 1181) proposed to homogenize the polyvinylidene fluoride (PVDF) fiber membrane prepared by electrospinning, and then construct an inverted pyramid microstructure by a template method to improve the sensitivity of the sensor to pressure; Ding Chen et al. prepared polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) fibers by electrospinning, which shrank after heat to form isotropic wrinkles with a scale of several microns. The co-shrinking silver nanowire (AgNWs) electrode can reach a tensile strain of 500%, showing great application potential in stretchable electrodes.
[0003] Although pre-stretching, template method, heat shrinkage and other methods can prepare micron-scale microstructures on the fiber membrane surface, secondary processing increases the complexity of the entire process. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a method for preparing a fiber membrane with a three-dimensional wrinkled microstructure, so that the two-dimensional fiber membrane product prepared by electrospinning is endowed with a three-dimensional wrinkled structure.
[0005] The first aspect of the present invention provides a method for preparing a fiber membrane having a three-dimensional wrinkled microstructure.
[0006] 1) dissolving the polymer in a corresponding solvent to prepare a uniform solution;
[0007] 2) Absorb an appropriate amount of solution, connect the metal needle to the high-voltage electrode of the electrospinning machine, and the receiving device is a liquid medium connected to another electrode of the spinning machine at the bottom, and the fiber membrane is collected on the water surface.
[0008] Furthermore, the distance between the metal needle and the surface of the liquid medium is 8 cm-23 cm.
[0009] Furthermore, the liquid medium is deionized water or an alcohol solution.
[0010] Furthermore, the alcohol solution is an aqueous solution of ethanol, and the volume ratio of water to ethanol is 9:1-6:4.
[0011] Furthermore, step 1 is to dissolve the thermoplastic polyurethane (TPU) raw material in N,N-dimethylformamide (DMF) solvent at 60° C. to obtain a uniform thermoplastic polyurethane spinning solution.
[0012] Furthermore, the concentration of the spinning solution is 5wt.%-25wt.%.
[0013] Furthermore, the electrospinning parameters of the electrospinning machine in step 2 are: the positive electrode voltage is 15 kV, the negative electrode voltage is 2 kV, the injection speed is 0.2 mm / min, and the time is 10 min; a 5 mL plastic syringe is used to absorb the solution, and the metal needle is a 21G metal needle with an outer diameter of 0.82 nm and an inner diameter of 0.51 nm, and the metal needle is connected to the positive electrode wire of the electrospinning machine.
[0014] The second aspect of the present invention provides a fiber membrane with a three-dimensional corrugated microstructure, which is prepared by the above method for preparing a fiber membrane with a three-dimensional corrugated microstructure.
[0015] The third aspect of the present invention provides an application of a fiber membrane with a three-dimensional wrinkled microstructure in a pressure sensor, comprising: branched carbon nanotubes are uniformly dispersed in ethanol with the assistance of ultrasound to prepare a dispersion with a concentration of 0.1 mg / mL, and 2 mL of the CNS dispersion is sprayed on the surface of the fiber membrane with a three-dimensional wrinkled microstructure prepared according to any one of claims 1 to 6 with a spray gun; after the ethanol evaporates, the TPU / CNS composite film is cut into a square of 1×1 cm2, and a copper electrode is attached to the edge of the conductive film with conductive silver glue; two identical composite films are overlapped with the surfaces sprayed with CNS to form a group of pressure sensors, and the edges are encapsulated with PDMS to obtain a pressure sensor.
[0016] The fourth aspect of the present invention provides an application of a fiber membrane with a three-dimensional corrugated microstructure in a strain sensor, wherein platinum nanoparticles are deposited on the surface of the fiber membrane with a three-dimensional corrugated microstructure prepared according to any one of claims 1 to 6 by an ion sputtering method to obtain a conductive composite film, and the ion sputtering conditions are a current of 60 mA, a pressure of 0.08 mbar, and a time of 10 min; the conductive composite film is cut into strips of 0.5×4 cm2, copper electrodes are pasted on both ends of the strips with conductive silver glue, and the electrodes are encapsulated with insulating tape to obtain a strain sensor.
[0017] The beneficial effects of the present invention are:
[0018] 1. It is only necessary to change the receiving device in the traditional electrospinning technology, that is, to change the solid receiving medium to a liquid (such as water or aqueous solution) receiving medium. The two-dimensional fiber membrane product prepared by electrospinning is endowed with a three-dimensional pleated structure. Due to the phase separation during the water receiving process, the polymer fiber precipitates on the water surface and releases the internal stress. The fluidity of the water surface allows the fiber to shrink freely and form a pleated structure.
[0019] 2. The construction of multi-level microstructure of fiber membrane helps to regulate the sensitivity of its composite material to stress and strain range, and improves the performance of fiber membrane in pressure sensor or strain sensor in a simple and controllable way. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a schematic diagram of the electrospinning structure of the present invention;
[0021] Figure 2 The microstructure of TPU fiber membrane when the receiving medium is (a) water / ethanol solution, (b) pure water and (c) aluminum foil;
[0022] Figure 3 (a) Stress-strain curves and (b) corresponding elongation at break and Young's modulus bar graphs of TPU fiber membrane when the receiving media are water / ethanol solution, pure water and aluminum foil, respectively;
[0023] Figure 4 The relative resistance change rate-strain curve diagram of the strain sensor corresponding to the fiber membrane prepared under different receiving media;
[0024] Figure 5 Surface microstructures of (a) P, (b) A, (c) W, (d) P-CNS, (e) A-CNS, and (f) W-CNS.
[0025] Figure 6 CLSM images of (a) P, (b) A, (c) W, (d) P-CNS, (e) A-CNS, and (f) W-CNS film surfaces;
[0026] Figure 7 (a) Surface roughness statistics and (b) water contact angle test results of TPU and TPU / CNS films;
[0027] Figure 8 (a) Pressure sensitivity of W-CNS, A-CNS and P-CNS pressure sensors, (b) Local magnified image of the pressure sensitivity test in the yellow box;
[0028] Fig. 9 Surface microstructures of TPU fiber membranes prepared by water reception when the receiving distance is (a) 8 cm, (b) 13 cm, (c) 18 cm, and (d) 23 cm;
[0029] Fig.10 The microstructure of the film prepared by water reception when the solution concentration is (a) 5wt.%, (b) 10wt.%, (c) 15wt.%, (d) 20wt.% and (e) 25wt.%, and the surface microstructure of the TPU film prepared by aluminum foil reception when the solution concentration is 15wt.%.
[0030] Fig.11 Surface microstructure of TPU fiber membranes prepared when the water / ethanol ratio in the receiving medium is (a) 9:1, (b) 8:2, (c) 7:3, and (d) 6:4. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical scheme and beneficial technical effects of the present invention clearer, the present invention is described in detail below in conjunction with specific implementation methods. The embodiments in this specification are only for explaining the present invention, not for limiting the present invention, and the parameters, proportions, etc. of the embodiments are selected according to actual conditions and have no substantial effect on the results.
[0032] The main measuring instruments are: the surface and cross-sectional micromorphology of the samples are characterized by field emission scanning electron microscope (FESEM, Nova NanoSEM450, Thermo Fisher Scientific, USA). All samples are treated with platinum spraying before testing, and the electron acceleration voltage is 5kV. The laser confocal microscope CLSM (LSM 700, Carl Zeiss AG, Germany) is used to characterize the roughness of the film surface, in reflection mode, 405nm wavelength laser scanning. The static water contact angle of TPU film and its composite materials is tested by optical contact angle tester (DSA25, KRUSS, Germany). The mechanical properties of TPU fiber membrane are tested by universal testing machine (5967, Instron, USA) in tensile mode, with a clamp spacing of 2cm. The sample is cut into strips of 0.5×4cm2, and the universal testing machine stretches the sample strip at a speed of 10mm / min until the sample breaks. The conductivity of the conductive composite material was tested by a digital power meter (2400, Keithley, USA) equipped with a four-probe instrument (RTS-2, Guangzhou Four Probe Co., Ltd.). Strain sensing performance test: The uniaxial tensile strain of the strain sensor was applied by a homemade small-scale stretching device. The two ends of the sensor were fixed on the clamp of the stretching machine, and the stretching device applied tensile stress of different rates or different strain ranges to the sample to be tested. During the test, the resistance change of the strain sensor was recorded by a digital power meter. Pressure sensing performance test: An exciter (TJZ 20, China Tester) was used to apply impact stress vertically to the sample to be tested. The pressure on the sample was introduced into an oscilloscope (PicoScope 3403D, PicoTechnology, USA) through the pressure sensor of the exciter, and the resistance change of the sample to be tested was read out by a digital power meter.
[0033] Specifications of reagents and chemicals: thermoplastic polyurethane (TPU), brand 1185A, purchased from BASF, Germany; N, N-dimethylformamide (DMF), analytical grade, purchased from Zhengzhou Piney Chemical Reagent Factory; ethanol, concentration 99.5%+, purchased from Shanghai Aladdin Reagent Co., Ltd.; branched carbon nanotubes (CNS), polyethylene glycol (PEG) coated, average diameter 14±4nm, length about 70μm, purchased from Cabot Corporation, USA; polydimethylsiloxane (PDMS), brand 184, purchased from Dow Corning, USA. All the above raw materials and reagents were purchased and used directly without further purification.
[0034] Example 1
[0035] Preparation method:
[0036] (1) First, dissolve the TPU pellets in DMF solvent, stir magnetically at 60°C for 2 hours, and prepare a uniform and transparent solution with a concentration of 25wt.%. Use a 5mL plastic syringe to absorb an appropriate amount of solution, and configure the syringe with a 21G metal needle (outer diameter 0.82nm, inner diameter 0.51nm), which is connected to the positive electrode wire of the electrospinning machine. Place the syringe on the corresponding card slot of the spinning machine, and adjust the receiving distance, that is, the distance between the metal needle and the surface of the liquid medium. The receiving device is a liquid medium whose bottom is connected to the negative electrode wire of the spinning machine. The TPU fiber membrane is usually collected on the surface of the liquid medium (such as Figure 1 ), the volume ratio of water / ethanol in the receiving medium is 6:4. The operating parameters of the electrospinning machine are: positive voltage is 15kV, negative voltage is 2kV, injection speed is 0.2mm / min, time is 10min, and receiving distance is 13cm. In addition, as a comparison, the receiving medium was changed under the same spinning parameters, and samples were prepared by receiving with pure water and conductive aluminum foil respectively.
[0037] (2) Preparation of strain sensor: First, platinum nanoparticles (PtNPs) were deposited on the surface of TPU film by ion sputtering, and the experimental conditions were current 60 mA, pressure 0.08 mbar, and time 10 min. The TPU / PtNPs conductive composite film was cut into strips of 0.5×4 cm2, and copper electrodes were attached to both ends of the strips with conductive silver glue, and the electrodes were encapsulated with insulating tape.
[0038] Performance Testing:
[0039] Figure 2 SEM images of TPU fiber membranes collected from water / ethanol solution, pure water and aluminum foil surfaces to change the receiving medium under the same electrospinning parameters. From the images, it can be observed that the surface of the fiber membrane received by the traditional solid receiving medium is relatively flat, while the surface of the fiber membrane received by the liquid medium is undulating and has a multi-level microstructure. This shows that the fluidity and wettability of the liquid receiving medium provide greater flexibility for the overlap of the fibers, which helps the fibers relax stress during the solidification process, resulting in shrinkage of the fiber membrane.
[0040] Figure 3 This is a comparison chart of the mechanical properties of fiber membranes prepared under different receiving media. It can be observed that when the receiving medium is changed from aluminum foil to liquid, the elongation at break of the fiber membrane increases and the modulus decreases. This is because when the film has a wrinkled microstructure, the fiber will undergo a morphological change from curved to straight during the stretching process, and this change can offset part of the strain. Therefore, the existence of a multi-level microstructure can reduce the modulus of the material and increase the elongation at break.
[0041] Figure 4The tensile strain sensing performance of sensors assembled with different fiber membranes. It can be seen that the strain sensor prepared with the fiber membrane with multi-level microstructure has a larger detection range, but the sensitivity (curve slope) at the same strain is lower. Therefore, the microstructure on the fiber membrane surface helps the strain sensor to have a wider detection range, which corresponds to the mechanical properties test results.
[0042] Example 2
[0043] Preparation method:
[0044] (1) First, dissolve the TPU pellets in DMF solvent, stir magnetically at 60°C for 2 hours, and prepare a uniform and transparent solution with a concentration of 15wt.%. Use a 5mL plastic syringe to absorb an appropriate amount of solution, and configure the syringe with a 21G metal needle (outer diameter 0.82nm, inner diameter 0.51nm), which is connected to the positive electrode wire of the electrospinning machine. Place the syringe on the corresponding card slot of the spinning machine, and adjust the receiving distance, that is, the distance between the metal needle and the surface of the liquid medium. The receiving device is a liquid medium whose bottom is connected to the negative electrode wire of the spinning machine. The TPU fiber membrane is usually collected on the surface of the liquid medium (such as Figure 1 ), the receiving medium is pure deionized water. The operating parameters of the electrospinning machine are: positive voltage is 15kV, negative voltage is 2kV, injection speed is 0.2mm / min, time is 10min, and receiving distance is 13cm.
[0045] (2) Preparation of pressure sensor: CNS was uniformly dispersed in ethanol with the assistance of ultrasound to prepare a dispersion with a concentration of 0.1 mg / mL. 2 mL of CNS dispersion was sprayed on the surface of TPU fiber membrane prepared by water reception with a spray gun. After the ethanol evaporated, the TPU / CNS composite film was cut into 1×1 cm2 squares, and copper electrodes were attached to the edges of the conductive film with conductive silver glue. Two identical composite films were overlapped with the surfaces sprayed with CNS to form a group of pressure sensors, and the edges were encapsulated with PDMS. In order to explore the difference in the response of sensors assembled from TPU films prepared by different processing methods to pressure, TPU films prepared by hot pressing and fiber membranes prepared by aluminum foil reception with a TPU solution concentration of 25 wt.% were used as control samples, and pressure sensors were assembled in the same way. Before spraying CNS, the TPU films prepared by water reception, aluminum foil reception, and press plate were named W, A, and P, respectively. After spraying CNS, they were named W-CNS, A-CNS, and P-CNS, respectively.
[0046] 2. Performance Testing
[0047] Figure 5(ac) are the surface microstructures of TPU films prepared by different processing methods. It can be seen that the surface of the film prepared by hot pressing is relatively smooth; the surface of the fiber membrane prepared by receiving with aluminum foil is relatively flat, and there are a large number of pores between the fibers; and the surface of the film with a beaded structure received by water has a large number of small balls, and the fibers are entangled on the fiber surface to form a folded structure. After spraying CNS dispersion ( Figure 5 df), a large number of CNSs entangled with each other can be observed on the film surface, and the gaps between the fibers are covered to some extent, but it can still be observed that the surface of the sample prepared by water reception is more uneven.
[0048] Figure 6 CLSM images of (a) P, (b) A, (c) W, (d) P-CNS, (e) A-CNS, and (f) W-CNS film surfaces. CLSM can quantitatively characterize the surface roughness of the film. Through tomography and imaging within a certain thickness range, it can be observed that the electrospinning and phase separation processes give the TPU film a rougher surface.
[0049] Figure 7 The following are the (a) surface roughness statistics and (b) water contact angle test results of TPU and TPU / CNS films. The surface roughness of TPU films before and after spraying CNS was statistically analyzed. It can be seen that CNS increases the roughness of P-CNS and W-CNS compared to P and W. However, the roughness of A-CNS is reduced compared to A, because CNS covers a large number of gaps between the original fibers. Similarly, the test of water contact angle (CA) also reflects the same trend as the roughness ( Figure 7 b). In general, the TPU membrane prepared by electrospinning-phase separation has a higher surface roughness, which will be more conducive to improving the sensitivity of pressure sensing.
[0050] Figure 8 (a) compares the pressure sensing performance of W-CNS, A-CNS and P-CNS sensors, and (b) is a partial enlarged view of the yellow box. From the trend of current change under different pressures in the figure, it can be seen that the P-CNS pressure sensor has the highest pressure sensing sensitivity in the pressure range of 0-0.074kPa, that is, S = 1.37kPa-1 (S = (ΔI / I0) / ΔP, where ΔI refers to the current change; I0 refers to the initial current; ΔP refers to the pressure change), but after exceeding this pressure range, the resistance hardly changes with the change of pressure. The sensitivity S of the A-CNS pressure sensor is 0.0035kPa-1 in the pressure range of 0-2.8kPa. After the pressure increases, the sensitivity increases slightly, but it is only about 0.0095kPa-1.
[0051] The sensitivity S of the W-CNS pressure sensor is 0.11 kPa-1 in the pressure range of 0-0.70 kPa; in the range of 0.7-14 kPa, S is 0.016 kPa-1. From the perspective of the entire pressure range, the W-CNS sensor has high sensitivity and a wide detection range. This is because the W surface has a multi-level microstructure, and the fibers are wrapped around the elastic polymer spheres, avoiding too many pores in the film, so that the surface structure of the composite material will change accordingly under different pressures, resulting in changes in the conductive path. Therefore, the multi-level rough structure composed of beads and wrinkles improves the performance of the pressure sensor.
[0052] Example 3
[0053] When the receiving distance is (a) 8 cm, (b) 13 cm, (c) 18 cm and (d) 23 cm, the surface microstructure of the TPU fiber membrane prepared by water reception is the same as in Example 2.
[0054] like Fig. 9 The microscopic morphology of TPU fiber membranes prepared at different receiving distances is shown, including (a) 8cm, (b) 13cm, (c) 18cm and (d) 23cm. It can be observed that when the receiving distance increases from 8cm to 23cm, the wrinkled structure on the surface of the fiber membrane gradually disappears, which shows that the residual amount of DMF in the fiber has a significant effect on the phase separation process. When the receiving distance is short, the solvent is not completely volatilized, the TPU fiber is not completely solidified, and the fluidity of the water surface has a greater impact on its final morphology.
[0055] Example 4
[0056] The microstructure of the film prepared by water absorption when the TPU solution concentration is (a) 5wt.%, (b) 10wt.%, (c) 15wt.%, (d) 20wt.% and (e) 25wt.%. (f) The surface microstructure of the TPU film prepared by aluminum foil absorption when the solution concentration is 15wt.%. The rest is the same as Example 2.
[0057] like Fig.10 The effect of TPU spinning solution concentration on the morphology of fiber membranes. When the concentration of TPU solution is very low (5wt.%), only polymer spheres can be collected. This is because the lack of entanglement between the macromolecular chains makes it difficult for the solution to solidify into filaments. As the concentration of the polymer solution increases, the microscopic morphology gradually evolves from a beaded structure to uniform fibers. When the concentration reaches 25wt.%, the TPU solution becomes very viscous, and the thickness of the prepared fibers is more uniform. When the concentration of the TPU solution is 15wt.%, the film prepared by water absorption is composed of spindle-shaped spheres of similar shape and size and fibers entangled in them ( Fig.10c), in addition to the beaded microstructure, the water absorption method causes the fibers to shrink and wrap around the surface of the polymer spheres, forming a larger scale wrinkled structure. For comparison, TPU films were prepared by aluminum foil absorption under the same conditions, such as Fig.10 f, it can be seen that even if the concentration of the polymer solution is the same, the surface microstructure of the prepared film is very different. The fiber membrane with a beaded structure prepared by aluminum foil reception did not shrink, and the entire film was flatter. Therefore, the phase separation process during water reception caused the fibers and polymer beads to entangle together and the entire film to shrink to form a wrinkled structure.
[0058] Example 5
[0059] The water / ethanol ratio in the receiving medium is (a) 9:1, (b) 8:2, (c) 7:3, and (d) 6:4, and the rest is the same as in Example 1.
[0060] like Fig.11 The surface microstructure of the TPU fiber membrane prepared when the water / ethanol ratio in the receiving medium is (a) 9:1, (b) 8:2, (c) 7:3, and (d) 6:4. The changes in the surface microstructure of the fiber membrane show that as the ethanol ratio increases, the looseness and wrinkle structure of the fiber membrane are different. This is because the surface tension coefficient of ethanol is much lower than that of water, resulting in better wettability of ethanol to TPU fibers and a faster phase separation process. As the ethanol ratio increases, the TPU fibers will change from forming a tight film at the beginning to being dispersed in the liquid to form loose fiber clusters.
[0061] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a fiber membrane with a three-dimensional wrinkled microstructure, characterized in that: 1) dissolving the polymer in a corresponding solvent to prepare a uniform solution; 2) Absorb an appropriate amount of solution, connect the metal needle to the high-voltage electrode of the electrospinning machine, and the receiving device is a liquid medium connected to another electrode of the spinning machine at the bottom, and the fiber membrane is collected on the water surface.
2. The method for preparing a fiber membrane with a three-dimensional wrinkled microstructure according to claim 1, characterized in that: The distance between the metal needle and the surface of the liquid medium is 8 cm-23 cm.
3. The method for preparing a fiber membrane having a three-dimensional wrinkled microstructure according to claim 1, characterized in that: The liquid medium is deionized water or an alcohol solution.
4. The method for preparing a fiber membrane with a three-dimensional wrinkled microstructure according to claim 1, characterized in that: The alcohol solution is an aqueous solution of ethanol, and the volume ratio of water to ethanol is 9:1-6:
4.
5. The method for preparing a fiber membrane with a three-dimensional wrinkled microstructure according to claim 1, characterized in that: The step 1 is to dissolve the thermoplastic polyurethane raw material in N,N-dimethylformamide solvent at 60° C. to obtain a uniform thermoplastic polyurethane spinning solution.
6. The method for preparing a fiber membrane with a three-dimensional wrinkled microstructure according to claim 5, characterized in that: The concentration of the spinning solution is 5wt.%-25wt.%.
7. The method for preparing a fiber membrane with a three-dimensional wrinkled microstructure according to claim 1, characterized in that: The electrospinning parameters of the electrospinning machine in step 2 are: positive electrode voltage is 15 kV, negative electrode voltage is 2 kV, injection speed is 0.2 mm / min, and time is 10 min; a 5 mL plastic syringe is used to absorb the solution, and the metal needle is a 21G metal needle with an outer diameter of 0.82 nm and an inner diameter of 0.51 nm, and the metal needle is connected to the positive electrode wire of the electrospinning machine.
8. A fiber membrane with a three-dimensional wrinkled microstructure, characterized in that: The fiber membrane is prepared by the method for preparing a fiber membrane with a three-dimensional wrinkled microstructure as described in any one of claims 1 to 6.
9. Application of a fiber membrane with a three-dimensional wrinkled microstructure in a pressure sensor, characterized in that: The method comprises uniformly dispersing branched carbon nanotubes in ethanol with the assistance of ultrasound to prepare a dispersion liquid with a concentration of 0.1 mg / mL, spraying 2 mL of the CNS dispersion liquid on the surface of a fiber membrane with a three-dimensional wrinkled microstructure prepared according to any one of claims 1 to 6 with a spray gun; cutting the TPU / CNS composite film into a square of 1×1 cm2 after the ethanol evaporates, and pasting a copper electrode on the edge of the conductive film with a conductive silver glue; overlapping two identical composite films with the surfaces sprayed with CNS to form a group of pressure sensors, and encapsulating the edges with PDMS to obtain a pressure sensor.
10. Application of a fiber membrane with a three-dimensional wrinkled microstructure in a strain sensor, characterized in that: A conductive composite film is obtained by depositing platinum nanoparticles on the surface of a fiber membrane with a three-dimensional wrinkled microstructure prepared according to any one of claims 1 to 6 using an ion sputtering method, wherein the ion sputtering conditions are a current of 60 mA, a pressure of 0.08 mbar, and a time of 10 min; the conductive composite film is cut into strips of 0.5×4 cm2, copper electrodes are attached to both ends of the strips with conductive silver glue, and the electrodes are encapsulated with insulating tape to obtain a strain sensor.
Citation Information
Patent Citations
Piezoelectric polymer fiber membrane with high piezoelectric property and preparation method thereof
CN114657705A
3-dimenstinal nanofiber membrane and Method of manufacturing the same using liquid collector
KR1020160139264A
Nonwoven structure and method of fabricating the same
US20110082565A1
Microstructure elastomer film and preparation method therefor, and flexible pressure sensor and preparation method therefor
WO2024031842A1
